Yeast culture as an additive in swine grower rations - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Adding yeast culture at manufacturer's recommended levels to a complete, pelleted, 16% crude protein ration fed to nursery-age pigs produced no measurable improvement in rate of gain, feed efficiency, survival, activity, or appearance.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Yeast; Grower rations; Nursery pigs